PENGARUH BRAND EXPERIENCE DAN BRAND LOVE TERHADAP KEPUTUSAN PEMBELIAN ULANG TEH BOTOL SOSRO DENGAN BRAND LOYALTY SEBAGAI VARIABEL MEDIASI DI KOTA PEKANBARU - Goval Melayu; Aida Nursanti; Sharnuke nukeAsrilsyak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
The increasingly intense competition in the ready-to-drink tea industry requires companies tomaintain consumers through the creation of positive brand experiences and strong emotionalconnections. Teh Botol Sosro, as a well-established brand, faces challenges in sustaining consumerloyalty and repurchase decisions, particularly in Pekanbaru City. This study aims to analyze theeffect of Brand Experience and Brand Love on Repurchase Decisions with Brand Loyalty as amediating variable. This research employs a quantitative approach using a survey method involving100 respondents who are consumers of Teh Botol Sosro in Pekanbaru City, selected throughpurposive sampling. Data were analyzed using Partial Least Square–Structural Equation Modeling(PLS-SEM) with the assistance of SmartPLS 4.0 software. The results indicate that BrandExperience and Brand Love have a positive and significant effect on Brand Loyalty and RepurchaseDecisions. Furthermore, Brand Loyalty is proven to act as a mediating variable that strengthens theinfluence of Brand Experience and Brand Love on Repurchase Decisions. The findings concludethat brand experience and emotional attachment play an important role in building consumerloyalty and encouraging repurchase decisions. The implications of this study are expected toprovide a reference for companies in formulating marketing strategies that focus on enhancingbrand experience and fostering long-term relationships with consumers.Keywords : Brand Experience, Brand Love, Brand Loyalty, Repurchase Decision